Optimizing the Ability of Aceh Province in Paradiplomacy Practice - Novialdi, Risky; Rassanjani, Saddam (Nation State: Journal of International Studies, 2020)
This paper analyzes the opportunities for the development of Aceh province in the era of globalization. Paradiplomacy is one of the efforts that can be utilized to develop the Aceh province. Based on the Constitution Number 11 of 2006 on the Aceh government, has given Aceh province considerable authority to develop its territory, including establishing diplomatic relations with the regions others abroad through the Paradiplomacy practice. But, with this considerable authority, Aceh is still the poorest region in Sumatra and the poorest number 6 in Indonesia based on the statistics centre data (BPS) in 2019. This means that Aceh still fails to exploit its social and natural conditions for the development of its territory. In This research we used  qualitative method, by gathering previous studies through observation, interviews and data collection. Aceh could utilize the "Tsunami Disaster" to become the initial capital to practice paradiplomacy with other regions abroad. Actually Aceh also has other capital, namely as a former conflict area and also as the best coffee producer in the world. Therefore, Aceh has at least three large capitals to establish cooperation with foreign parties through the paradiplomacy practice, with the concept of sister Province, Sister City.